Follicular-fluid anti-Mullerian hormone (FF AMH) is a plausible biochemical indicator of functional viability of oocyte in conventional in vitro fertilization (IVF) cycles - Bindu N Mehta; Meena N Chimote; Nishad N Chimote; Nirmalendu M Nath; Natachandra M Chimote (Wolters Kluwer Medknow Publications, 2013)
Context: Oocyte quality may be a governing factor in influencing in vitro fertilization (IVF) outcomes. However, morphological evaluation of oocyte quality is difficult in conventional IVF cycles. Follicular-fluid (FF), the site for oocyte growth and development, has not yet been sufficiently explored to obtain a marker indicative of oocyte quality. Anti-Mullerian hormone (AMH) is produced by granulosa cells of preantral and early-antral follicles and is released in FF. Aim: To investigate AMH as a biochemical indicator of functional viability/quality of oocyte produced in the FF micro-environmental milieu. Settings and Design: Prospective study involving 132 cycles of conventional IVF-embryo transfer (ET) in infertile women. Subjects and Methods: AMH concentration was estimated in pooled FF on day of oocyte pickup. Cycles were sorted into low and high groups according to median (50 th centile) values of measurement. Main outcome measure was oocyte viability, which included morphological assessment of oocyte quality, fertilization rate, clinical pregnancy, and implantation rates. Statistical Analysis: Graph-pad Prism 5 statistical package. Results: Low FF AMH group shows significantly higher percentage of top-quality oocytes (65.08 ± 24.88 vs. 50.18 ± 25.01%, P =0.0126), fertilization (83.65 ± 18.38 vs. 75.78 ± 21.02%, P =0.0171), clinical pregnancy (57.57 vs. 16.67%, P <0.0001), and embryo implantation rates (29.79 vs. 7.69%, P <0.0001) compared to high FF AMH group. FF AMH shares an inverse correlation with FF E2 (Pearson r = −0.43, r 2 = 0.18) and clinical pregnancy (Pearson r = −0.46, r 2 = 0.21). Threshold value of FF AMH for pregnancy is <1.750 ng/mg protein. Conclusion: FF AMH is a plausible biochemical indicator of functional viability of oocyte in conventional IVF cycles.